Engineering high-performance CTAB-functionalized magnesium silicate nano-adsorbent for efficient removal of Cd2+, Co2+, and Cu2+ from single-metal aqueous solutions - Shemy, Marwa H.; Mohamed, Reham A.; Abdel-Khalek, Ahmed A.; Alqhtani, Haifa A.; Al Zoubi, Wail; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2025)
The development of highly efficient, recyclable adsorbents for heavy metal remediation remains a critical challenge in environmental engineering. This study introduces a novel cetyltrimethylammonium bromide-functionalized magnesium silicate (CTAB/MS) nano-adsorbent was synthesized through a multi-step surface modification of serpentinite involving intercalation with dimethyl sulfoxide, methanol treatment, and CTAB incorporation. The resulting nanostructure was extensively characterized and applied for the removal of cadmium (Cd2+), cobalt (Co2+), and copper (Cu2+) ions from contaminated water. The characterization findings confirmed significant morphological and structural modifications, including enhanced surface area, functional group availability, and mesoporosity, which contributed to enhanced adsorption performance. The kinetic modeling confirmed that the process predominantly followed a pseudo-first-order model, suggesting that rapid physisorption mechanisms controlled the initial adsorption phase. Equilibrium studies revealed that adsorption followed the Langmuir isotherm model, indicating monolayer adsorption on homogeneous active sites, with maximum adsorption capacities of 491.9 mg/g (Cd2+), 481.8 mg/g (Co2+), and 434.3 mg/g (Cu2+) at 303 K. Furthermore, statistical physics-based isotherm model incorporating steric and energetic parameters provided deeper mechanistic insights. The adsorption energy (ΔE) values remained below 12.66 kJ/mol, confirming a predominantly physical adsorption process, while thermodynamic analysis indicated an exothermic and spontaneous nature, as evidenced by negative free enthalpy (G) and internal energy (Eint) values. The recyclability assessment demonstrated that CTAB/MS retained over 70% of its adsorption efficiency after five consecutive regeneration cycles, underscoring its long-term applicability in water treatment. This highlights the potential of CTAB/MS as an advanced, cost-effective, and sustainable solution for large-scale water purification.